DESIGN ENGINEERING DETAIL OF SONO (OPAK RIVER) MICROHYDRO IRRIGATION PROJECT PARANGTRITIS KRETEK VILLAGE IN THE DISTRICT OF BANTUL OF YOGYAKARTA - Arief Budiyanto (ASEAN Journal of Systems Engineering, 2015)
Bantul  District  has  many  small  river  which  have the potency to  be  converted  to  electrical energy.  This  research  aims at  determination  the  potency  of  hydropower  and  designing  very low  head  water  power  plant.  The  observational  step  started  by measuring head and flow rate.  Designing of water turbine should be  considered  the  power  available.  Since  the  turbine  usually  run at low speed and the generator speed is quite high (1500 rpm) it require   speed  increaser.  Based  on  primary  data,  the electrical power can be generated up to  41.02  kilowatt kW  .The project’s objective is to provide the village Irrigation Sono (Opak river) Parangtritis with a  reliable,green clean  and  economically viable source of electrical energy. A potential  hydropower  site  in  the  vicinity  of  the  villages was identified at Opak river. The  salient  features  of  the  scheme  are  summarised  as follows: Gross Head (Hgross) 2- 3.5 m , Net Head ( Hnett)  2.5 m, Flow River 4,48 m3 /s, Design of flow rate (Q)  =2.5 m 3/s.  Electrical Power (Pelg) 61,31 KW. The project comprises of the following components: Water  intake  and  conveyance  structures,  including sand trap,  headrace  canal,  forebay, draft tube  and tailrace. Powerhouse, including protection wall  Generating  equipment, comprising  of  a  propeller turbine and synchronous generator  Electrical  turbine  control  system,  ELC  (Electronic Load Controller)  Transmission  facilities.The  implementation  of  the  project  will  take approximately six to eight months including the finalisation of  the  preparatory  work (detailed  design,  tendering, contract  awarding),  actual  implementation  of  the  project, testing, commissioning and training of operators.  Two villagers will be assigned and trained as operators for the operation and maintenance of the plant. In  order  to  optimize  the  viability  of  the  water source office of  Bantul, load management  is  deemed  necessary  to  optimise  the  supply and  demand  situation,  such  as  using  energy   pump for irrigation.